PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP EMPLOYEE ENGAGEMENT PADA KARYAWAN BAGIAN MEDIS RSKIA SADEWA YOGYAKRATA - Wasiman Wasiman (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study was to describe (1) the influence of compensation on employee engagement(2) the influence of work environment on employee engagement and (3) the influence of compensationand work environment on employee engagement at medical employee RSKIA Sadewa Yogyakarta.This is a quantitative research by using a questionnaire. The population of the research was 93employees and the sample of the research was 75 employees. The data analysis techniques usingnormality test, multicollinearity test, heteroscedasticity, multiple regression analysis, F-test and Ttest.The results show that: (1) compensation has no effect to employee engagement; (2) workenvironment has no effect to employee engagement and (3) compensation and work environmentsimultaneously affecting employee engagement.